Use of thapsigargin to study Ca2+ homeostasis in cardiac cells. Issue 5 (October 1995) - Rogers, Terry B.; Inesi, Giuseppe; Wade, Robert; Lederer, W. J.
Abstract : Several reports have documented that thapsigargin is a potent inhibitor of the SR Ca 2+ ATPase isolated from cardiac or skeletal muscle. We have characterized the specificity of this agent in intact rat cardiac myocytes using cells maintained in the whole cell voltage clamp configuration. We have shown that thapsigargin decreases the magnitude of the Ca 2+ transient and the twitch by about 80% while it slows the decay rate for these responses. These changes were not accompanied by any alterations in sarcolemmal currents or in the trigger Ca 2+ generated by the inward calcium current. Taken together these results reveal that the action of thapsigargin is restricted to the SR Ca 2+ ATPase in intact cardiac myocytes. Furthermore, it is demonstrated unambiguously that SR intracellular Ca 2+ stores are an absolute requirement for the development of contractile tension in rat heart myocytes. It is shown that thapsigargin is a valuable probe to examine the importance of SR pools of Ca 2+ and the role of the Ca 2+ ATPase in intact myocytes as well as in genetically altered heart cells.